CRYPTO-ASSETS AND TOKENS: THE NEED TO FILL GAPS IN THE LEGISLATION OF UZBEKISTAN (World Conference on Social Sciences, Law and Public Policy, 2026)
The rapid development of the digital economy is causing fundamental changes in modern financial systems. In particular, crypto-assets and tokens based on blockchain technology are becoming an integral part of global economic relations. Their emergence not only created new investment instruments, but also made it possible to carry out operations without financial intermediaries. At the same time, these new institutions pose complex legal problems for states. Despite the fact that a number of regulatory legal acts have been adopted in the Republic of Uzbekistan to regulate the circulation of crypto-assets, there are still significant legal gaps in this area. Does it enter circulation as a commodity? Does it function as money? Or is it a new form of digital property? These questions attracted not only economists and lawyers, but also regulators, investors, and the public, turning the unique process of crypto-asset formation into a complex field of scientific discussion.